Systematic literature review of learning strategies for Arabic speaking skills among non-native speakers - Haryati Yaacob; Nik Mohd Rahimi Nik Yusoff; Harun Baharudin; Hafizhah Zulkifli (Penerbit Universiti Kebangsaan Malaysia, 2024)
Arabic as a second language is an essential component of modern education. Speaking abilities are a crucial aspect of language mastery and play a crucial role in ensuring effective communication. However, there are still a significant number of students who are unable to adequately master speech skills. This issue has prompted numerous researchers to investigate strategies for acquiring abilities to speak. However, few scholars place a systematic literary emphasis on this subject. In order to resolve the identified issues, the purpose of this article is to examine the emphasis of systematic literature on recent studies concerning Arabic-speaking skills learning strategies among non-native speakers. This SLR writing procedure has referenced the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) writing standard. Four primary databases, Web of Science, Scopus, SAGE, and ERIC, were used to locate the articles and related resources included in this SLR. Based on thematic analysis, there are four primary themes in this SLR: 1) Cognitive 2) Teaching aids 3) Communication Strategy, and 4) Behavior. In order to improve speaking skills to a high level, the study recommends the use of learning strategies for speech skills practised in learning.